Flexor Tendon Pulley Injuries: A Systematic Review of the Literature and Current Treatment Options - Artiaco, Stefano; Bosco, Francesco; Lusso, Alessandro; Cioffi, Luigi Luca; Battiston, Bruno; Massè, Alessandro (Journal of Hand and Microsurgery, 2022)
Closed injuries of the finger flexor pulley system are rare among the general population, and most of them occur during rock climbing. During the last few decades, scientific interest on this topic has increased. We conducted a systematic review of the literature according to the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines. The research was limited from January 2000 to March 2022. PubMed and Scopus databases were investigated for full-text articles published in English, French, and Italian using the following MeSH terms: ([pulley rupture] OR [finger pulley lesion]) AND ([injur*] OR [ruptur*] OR [damage] OR [trauma*]). Initial screening results identified 461 studies, among which 172 were included after including additional records identified through other sources and excluding repeated studies. Finally, four clinical studies were included in the analysis. The methodological quality of the articles was evaluated through the methodological index for nonrandomized studies (MINORS) score. Our search identified four studies that enrolled a total of 189 patients, of whom 164 were male and 25 were female. We finally examined 154 patients with a total of 208 pulleys damaged. Except for the thumb, all fingers were involved. Depending on the type of flexor pulley injury, graded with Schöffl classification, 69 patients underwent a surgical procedure, whereas 85 patients were treated conservatively. Closed finger pulleys injury occurred in rock climbers and non ̶ rock climbers. All patients had excellent results on the Buck-Gramcko score regardless of the return to sports activity. Considering the overall outcomes of the reviewed articles, functional results were satisfactory in both conservative and surgical treatment. Moreover, in grade 3 and 4, surgical results were positive regardless of the specific technique used for finger pulley reconstruction. Only minor complications were reported. Closed flexor tendon pulley injuries require a careful clinical and imaging examination to confirm the diagnosis. In most cases, positive clinical results can be achieved with either conservative or surgical therapy.
Keywords: bowstringing; flexor tendon; pulley reconstruction; pulley rupture; rock climbing